MONITORING OF Cacatua sulphurea abbotti POPULATION IN MASAKAMBING ISLAND, INDONESIA - Dudi Nandika; Yeni Aryati Mulyani; Dewi Malia Prawiradilaga; Dwi Agustina (BIOTROPIA, 2020)
The Critically Endangered Cacatua sulphurea abbotti is a unique subspecies of cockatoo, endemic to a single tiny Masakambing Island in Indonesia. Data procurement on the status and distribution of their wild population is urgently needed to determine the best conservation strategy for this species. Data were collected annually from 2008–2018 using a direct roost count method in a roosting tree. Only 10 cockatoos were recorded in 2008, but the number increased to 22 birds in 2018 (a 42.86% increase in a decade). The population was distributed across about 71% of the total area of the island, concentrated in the north-western part with a density of 1.56 (~2 birds/km²) in 2008, which increased to 3.44 (~3 birds/km²) in 2018. The zero-trapping policy enforced by the local government was likely effective in preventing population decline, although the population remains vulnerable due to nesting failure, presumably low genetic quality, and habitat destruction.